Respuesta :

Answer:

[tex] \rm T = \dfrac{6 B + 4}{R} [/tex]

Step-by-step explanation:

[tex] \rm Solve \: for \: T: \\ \rm \longrightarrow B = \dfrac{R T - 4}{6} \\ \\ \rm B = \dfrac{R T - 4}{6} \: is \: equivalent \: to \: \dfrac{R T - 4}{6} = B : \\ \rm \longrightarrow \dfrac{R T - 4}{6} = B \\ \\ \rm Multiply \: both \: sides \: by \: 6: \\ \rm \longrightarrow R T - 4 = 6 B \\ \\ \rm Add \: 4 \: to \: both \: sides: \\ \rm \longrightarrow R T = 6 B + 4 \\ \\ \rm Divide \: both \: sides \: by \: R: \\

\rm \longrightarrow T = \dfrac{6 B + 4}{R} [/tex]